2011
DOI: 10.1007/s12291-011-0137-z
|View full text |Cite
|
Sign up to set email alerts
|

Acid Phosphatase as a Marker in Malaria

Abstract: The serum acid phosphatase (ACP) activity and Hemoglobin (Hb) levels were measured in malaria patients and nonmalarial fever patients. The results were compared with normal healthy control subjects. ACP was significantly increased (P \ 0.001) in all the malaria patients. ACP was significantly higher in Plasmodium falcifarum malaria and mixed malaria when compared to Plasmodium vivax malaria. Hb levels were significantly decreased in all the malaria patients which indicates that malaria parasite uses host eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Similar findings were noted by D'Souza B et al, Garba IH et al, Daniel E et al, Pratinidhi SA et al [4][5][6][7] It has been reported that the red blood cells contain an excess quantity of ACP. The cell membrane plays a central role in the growth and propagation of the malarial parasite in the blood.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were noted by D'Souza B et al, Garba IH et al, Daniel E et al, Pratinidhi SA et al [4][5][6][7] It has been reported that the red blood cells contain an excess quantity of ACP. The cell membrane plays a central role in the growth and propagation of the malarial parasite in the blood.…”
Section: Discussionsupporting
confidence: 84%
“…Our study also shows statistically significant decrease in heamoglobin (Hb) levels between the malarial and non-malarial fever patients. Similar findings were also noted by D'Souza B et al, Kanwar G et al, Garba IH et al, Pratinidhi SA et al [6,7,14,15] .…”
Section: R -Opo 3 +Acceptor --------R -Oh + Acceptor-posupporting
confidence: 84%
“…Its levels are increased in various diseases like prostate cancer that has spread to the prostate gland and to the bone, Paget's disease, hemolytic anemia, prostatitis, thrombophlebitis, Gaucher's disease, hyperparathyroidism etc. which helps in their diagnosis [6] . Lysosomal and prostatic enzymes are inhibited by tartarate ions whereas erythrocytic and bone isoenzymes are not [7] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary health impacts caused by all forms of malaria is hemolytic anemia (i.e., severe malarial anemia) caused by the massive, simultaneous destruction of parasitized and unparasitized red blood cells (Sherman, 1998). Moreover, recent biomedical research has suggested that malarial hemolysis may impact the skeleton through acid phosphatase, free heme, and hemozoin release into the bloodstream (D'Souza et al, 2011;Moreau et al, 2012). Moreover, recent biomedical research has suggested that malarial hemolysis may impact the skeleton through acid phosphatase, free heme, and hemozoin release into the bloodstream (D'Souza et al, 2011;Moreau et al, 2012).…”
Section: Malaria Disease Dynamics and Pathophysiologymentioning
confidence: 99%
“…Such hemolytic anemia in malaria has been implicated in skeletal expansion of the marrow space (Walker et al, 2009). The chemical release is higher in falciparum and mixed malarial infections (D'Souza et al, 2011), and causes an imbalance in bone remodeling through simultaneous osteoclast stimulation and osteoblast impairment (Moreau et al, 2012). The chemical release is higher in falciparum and mixed malarial infections (D'Souza et al, 2011), and causes an imbalance in bone remodeling through simultaneous osteoclast stimulation and osteoblast impairment (Moreau et al, 2012).…”
Section: Malaria Disease Dynamics and Pathophysiologymentioning
confidence: 99%